Leukocyte-Derived Interleukin-10 Aggravates Postoperative Ileus - Stein, Kathy; Lysson, Mariola; Schumak, Beatrix; Vilz, Tim; Specht, Sabine; Heesemann, Jürgen; Roers, Axel; Kalff, Jörg C.; Wehner, Sven (Frontiers in Immunology, 2018)
Objective: Postoperative ileus (POI) is an inflammation-mediated complication of abdominal surgery, characterized by intestinal dysmotility and leukocyte infiltration into the muscularis externa (ME). Previous studies indicated that interleukin (IL)-10 is crucial for the resolution of a variety of inflammation-driven diseases. Herein we investigated how IL-10 affects the postoperative ME inflammation and found an unforeseen role of IL-10 in POI. Design: POI was induced by a standardized intestinal manipulation (IM) in C57BL/6 and multiple transgenic mouse strain including C-C motif chemokine receptor 2-/-, IL-10-/- and LysMcre/IL-10fl/fl mice. Leukocyte infiltration, gene and protein expression of cytokines, chemokines and macrophage differentiation markers as well as intestinal motility were analyzed. IL-10 serum levels in surgical patients were determined by ELISA. Results: IL-10 serum levels were increased in patient after abdominal surgery. In mice, a complete or leucocyte-restricted IL-10 deficiency ameliorated POI and reduced the postoperative ME neutrophil infiltration. Infiltrating monocytes were identified as main IL-10 producers and undergo IL-10-dependent M2 polarization. Interestingly, M2 polarization is not crucial to POI development as abrogation of monocyte infiltration did not prevent POI due to a compensation of the IL-10 loss by resident macrophages and neutrophils. Organ culture studies demonstrated that IL-10 deficiency impeded neutrophil migration toward the surgically traumatized ME. This mechanism is mediated by reduction of neutrophil attracting chemokines. Conclusion: Monocyte-derived macrophages are the major IL-10 source during POI. An IL-10 deficiency decreases the postoperative expression of neutrophil-recruiting chemokines, consequently reduces the neutrophil extravasation into the postsurgical bowel wall and finally protects mice from POI.